Membangun Negara Indonesia Berdasar Nilai-Nilai Luhur yang terkandung di dalam Syair Lagu Kebangsaan Indonesia Raya - Akwan, Umbu Nusa Putra (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to explore the noble values contained in the verses of the national anthem Indonesia Raya as a guideline in the development of the Indonesian nation. Through the approach of exegesis analysis and melodic movement, this study identifies the deep meaning in the lyrics of songs that have only been considered ceremonial symbols. The results of the study show that Indonesia Raya is not just a national anthem, but also contains a call for unity, struggle, and national development based on noble values. The phrase